Role of artificial intelligence in moderating the innovative financial process of the banking sector: a research based on structural equation modeling - Rabbani, M. R.; Lutfi, A.; Ashraf, M. A.; Nawaz, N.; Ahmad Watto, W. (Frontiers in Environmental Science, 2023)
This study seeks to find the moderating role of AI in the association between a bank’s innovative financial process and the bank’s market share. The data were analyzed using SPSS and SmartPLS software. The estimations were performed using structural equation modeling estimation techniques such as the measurement model, outer loading, convergent validity, discriminant validity, and SEM estimations. The initial estimations indicated factor as well as construct reliability and validity. The study concluded that an innovative financial process plays a vital role in enhancing the bank’s market share. However, artificial intelligence could not significantly moderate the relationship. The policymakers in the banking industry of Pakistan need to consider the up-gradation in the system of their financial process by innovation and artificial intelligence usage awareness in their existing staff as well their banking customers. Future research may include a similar model for Islamic as well as commercial banks in a comparative model. Additionally, future research may also include more banks as innovative financial institutions to get a greater sample size for a possible influence of artificial intelligence.